Subordinated debt and bank capital reform - Douglas D. Evanoff; Larry D. Wall (Federal Reserve Bank of Atlanta, 2000)
In recent years there has been a growing realization that there are significant problems with the current bank risk-based capital guidelines. As financial firms have become more sophisticated and complex they have effectively arbitraged the existing capital requirements. They have become so good at avoiding the intent of capital regulation that the regulations have essentially ceased to be a safety and soundness issue for supervisors and have become more a compliance issue. There is also a growing realization that bank regulation must more effectively incorporate market discipline to encourage prudent risk management. One means recommended to accomplish this is to increase the role of subordinated debt in the bank capital requirement. Arguments have been made that this could lead to improvements in both market and supervisory discipline. Although a number of such proposals have been made, there appears to be significant misunderstanding of how bank capital requirements would be modified and what might be accomplished by the modification. On the one extreme, some discussions of sub-debt seem to imply that merely requiring banks to issue debt would solve all safety and soundness related concerns. At the other extreme are a series of questions that raise doubts as to whether any change in the role of sub-debt could contribute toward safety and soundness goals. ; The goal of this article is to provide a comprehensive review and evaluation of the purpose and potential of subordinated debt proposals and to present a regulatory reform proposal that incorporates what we believe are the most desirable characteristics of subordinated debt. The article is intended as a reference piece from which readers new to the topic may find a thorough review of the issues, and others can draw on specific aspects of the debate. Coverage includes (1) a discussion of the characteristics of sub-debt that make it attractive for imposing market and supervisory discipline on banks; (2) explanation of how current regulatory arrangements do not allow these features to be fully utilized; (3) discussion of the role of debt markets, equity markets, and supervision in disciplining firm behavior, and how the use of sub-debt avoids many of the problems associated with alternative regulatory proposals; (4) a review of the evidence on the extent of market pricing and disciplining of risk imposed by holders of bank liabilities; (5) a review of some of the existing sub-debt proposals emphasizing their differences and the reasoning for those differences; (6) a new regulatory reform proposal which increases the role of sub-debt; and (7) a discussion of some of the standard questions raised about sub-debt proposals and, when appropriate, explanation of how our proposal addresses these concerns.
Keywords: 330; Debt; Bank capital; Bank liabilities; Bank supervision